The Influence of Advertising, Sales Promotion, and Service Quality on Customer Loyalty of Bank Jatim Indonesia - Novi Nurlaini; Joko Suyono; Damarsari Ratnasahara Elisabeth; Abdul Thalib Bin Bonn (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Customer loyalty is very important in a very tough business competition because loyalty will benefit the company's long-term development. To get customer loyalty, companies need to do the right marketing strategy so that it can affect customer loyalty. The purpose of this study is to analyze the influence of advertising, sales promotion and service quality on customer loyalty at Bank Jatim Indonesia, Branch of Dr. Soetomo Hospital Surabaya. The population in this study was 2,155 customers, the number of samples using the Slovin formula was 96. The data analysis technique used was multiple regression analysis. The research results are: 1) There is an influence of advertising on customer loyalty at Bank Jatim Branch of Dr. Soetomo Hospital Surabaya, 2) There is an influence of sales promotions on customer loyalty at Bank Jatim Branch of Dr. Soetomo Hospital Surabaya, 3) There is an influence of service quality on customer loyalty at Bank Jatim Branch of Dr. Soetomo Hospital Surabaya, 4) There is an influence of advertising, sales promotion and service quality simultaneously on customer loyalty at Bank Jatim Branch of Dr. Soetomo Hospital Surabaya, 5) Among the variables of advertising, sales promotion and service quality, the sales promotion variable has a dominant influence on customer loyalty at the Bank Jatim Branch of Dr. Soetomo Hospital Surabaya.